1970
DOI: 10.1111/j.1476-5381.1970.tb12898.x
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for studying the peristaltic reflex in the isolated colon

Abstract: Summary1. A method is described for studying the peristaltic reflex in the guinea-pig or cat isolated colon, using a graded localized intraluminal stimulus consisting of a solid bolus. 2. The method gives an easy evaluation of propulsive activity and makes it possible to record simultaneously the segmental activity of the circular muscle in relation to the site of stimulation and the contractions and relaxations of the longitudinal muscle coat.3. The velocity of propulsion, which is a reliable measure of propu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1970
1970
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…By analysing the pattern of the reflex in the isolated colon (Frigo & Lecchini, 1970), we can distinguish in the response of the longitudinal muscle coat a phasic contraction, which develops before the start of propulsion, and a tonic contraction, which increases in magnitude as propulsion progresses. Since both phases are blocked by tetrodotoxin and ganglion-blocking drugs, the nerve fibres and the ganglion cells of the intramural plexus are involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By analysing the pattern of the reflex in the isolated colon (Frigo & Lecchini, 1970), we can distinguish in the response of the longitudinal muscle coat a phasic contraction, which develops before the start of propulsion, and a tonic contraction, which increases in magnitude as propulsion progresses. Since both phases are blocked by tetrodotoxin and ganglion-blocking drugs, the nerve fibres and the ganglion cells of the intramural plexus are involved.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were carried out in the guinea-pig and in the cat by the method described in the preceding paper (Frigo & Lecchini, 1970).…”
Section: Methodsmentioning
confidence: 99%
“…Myenteric neurones are known to contain neural pathways responsible for peristalsis of the intestine (reviewed by Kosterlitz & Lees, 1964;North, 1982). These neuronal pathways have been studied by inflation of a small balloon in the intestine (Frigo & Lecchini, 1970) or by mechanical distension (Costa & Furness, 1976) to produce a localized stimulus. Hirst & McKirdy (1974) demonstrated the presence of a descending neural pathway in the guinea-pig small intestine excited by distension of the intestinal wall or transmural electrical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that PN stimulation enhances colonic peristalsis in response to balloon distension while sympathetic stimulation inhibits colonic peristalsis of the guinea pig distal colon in vitro. 36,37 However, it remains unclear whether PN stimulation affects fecal pellet propulsion or luminal pressure changes. As shown in Supplementary Video 2, we have clearly demonstrated that PN stimulation accelerates pellet propulsion.…”
Section: Discussionmentioning
confidence: 99%